Linguistik Struktural: Analisis Proses Morfofonemik dalam Karya Tulis Ilmiah Siswa Kelas IX SMP Al-Zahra Indonesia: Structural Linguistics: Analysis of Morphophonemic Processes in Scientific Papers of Grade IX Studentds of Al-Zahra Junior High School - Farhana, Ika; Anwar, Miftahulkhairah (Kibas Cenderawasih, 2023)
This research discusses the object of language research, namely word formation through morphophonemic processes. This study aims to determine the process of morphophonemic formation in the scientific papers of grade IX students of SMP Al-Zahra Indonesia. The method used is a qualitative descriptive method and the results of the analysis indicate the presence of morphophonemic processes in the work. Factors that cause this process include the bilinguality of speakers, insufficient vocabulary and unfaithfulness in using Indonesian.